PENGARUH STRATEGI PEMASARAN DALAM MENINGKATKAN VOLUME PENJUALAN PRODUK TAWAS HILYA - Habil Hasan; Lusi Endang Sri D; Ahmad Hafas Rasyidi (MANAJEMEN, 2025)
This study aims to determine how the 4P marketing strategy is applied to Tawas Hilya products and to identify the role of Shopee in increasing the sales volume of Tawas Hilya products. The approach used in this study is a qualitative approach. Data was collected through direct observation, in-depth interviews with business owners, employees, and several consumers, as well as documentation from product packaging. The research findings indicate that Tawas Hilya products have good quality in terms of packaging, brand, and logo. The price of Tawas Hilya is also very affordable considering the size and weight of the product. Tawas Hilya products are well-known and their sales have increased because they are sold through the Shopee app by sharing sales links on various social media platforms such as Facebook, Instagram, and WhatsApp.